Facile Fabrication of an Ammonia-Gas Sensor Using Electrochemically Synthesised Polyaniline on Commercial Screen-Printed Three-Electrode Systems - Korent, Anja; Žagar Soderžnik, Kristina; Šturm, Sašo; Žužek Rožman, Kristina; Redon, Nathalie; Wojkiewicz, Jean-Luc; Duc, Caroline (Sensors (Basel, Switzerland), 2021)
Polyaniline (PANI) is a conducting polymer, widely used in gas-sensing applications. Due to its classification as a semiconductor, PANI is also used to detect reducing ammonia gas (NH3), which is a well-known and studied topic. However, easier, cheaper and more straightforward procedures for sensor fabrication are still the subject of much research. In the presented work, we describe a novel, more controllable, synthesis approach to creating NH3 PANI-based receptor elements. The PANI was electrochemically deposited via cyclic voltammetry (CV) on screen-printed electrodes (SPEs). The morphology, composition and surface of the deposited PANI layer on the Au electrode were characterised with electron microscopy, Fourier-transform infrared spectroscopy and profilometry. Prior to the gas-chamber measurement, the SPE was suitably modified by Au sputtering the individual connections between the three-electrode system, thus showing a feasible way of converting a conventional three-electrode electrochemical SPE system into a two-electrode NH3-gas detecting system. The feasibility of the gas measurements’ characterisation was improved using the gas analyser. The gas-sensing ability of the PANI-Au-SPE was studied in the range 32–1100 ppb of NH3, and the sensor performed well in terms of repeatability, reproducibility and sensitivity.